Analysis of Bigo Live Application Abuse as a Form of Copyright Infringement - Acta Yoga Pratama (IHSA Institute, 2019)
Bigo Live as one of the broadcast applications in the form of live streaming video for android smartphone users can be misused and become a violation of copyright in the field of copyrighted films (cinematography). The actor recorded a film that was being shown in theaters and the film was broadcast live using the Bigo Live application. Research problems: (1) What are the legal consequences of the abuse of the Bigo Live application in cinema as a violation of the copyright protection of a film (cinematography)? (2) What is the criminal responsibility for the perpetrators who violate the copyright protection of a film (cinematography)? The problem approach used in this study is empirical juridical, with speakers from Bandar Lampung Police and Criminal Law Lecturers at the Faculty of Law. Data collection through literature studies and field studies. Data analysis is done qualitatively. The results of this study indicate: (1) The legal consequences of the abuse of the Bigo Live application in cinema as a form of violation of the copyright protection of a film (cinematography) include the legal consequences for the perpetrators and legal consequences for copyright holders. The legal consequence for the perpetrator is that the perpetrator can be subject to criminal sanctions, either imprisonment or fines for violations committed without the right to broadcast the film through the Bigo Live application. Meanwhile the legal consequences for the copyright owners are to obtain legal protection for violations of their copyright rights that are misused by others. (2) Criminal liability against perpetrators who commit violations of copyright protection of a film (cinematography) is based on an element of error and intentional conduct, the ability of the defendant to be responsible, there is no justification and forgiving for the defendant in violating the protection of rights copyright a film (cinematography). Suggestions for research are: (1) The public who use internet-based media applications to be morewise and responsible in using the media (2) The criminal responsibility for the perpetrators of crimes in order to provide guidance efforts so as not to repeat their mistakes in the future.